The Language of Sadness: How Teens Express Sad Emotions Through Words - Mahesa, Ajeng; Amelia, Alya; Rakhman, Ifan; Nurmaliha, Nabila; Adiba, Rahma; Rizkyanfi, Whilky (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2024)
This study aims to understand how adolescents express their sadness, both through language as verbal communication and through nonverbal communication. This research focuses on analyzing the expression of sad emotions through language using a psycholinguistic approach, determining the frequency of sad language use, identifying factors that often trigger the use of sad language, and comparing the use of verbal and nonverbal communication in expressing sad emotions. The data collection method of this research is descriptive-qualitative from a survey in the form of a questionnaire distributed to teenagers aged 12 to 21 years through social media. Respondents to the questionnaire were as many as 107 adolescents, with details of 21.5% early adolescents (12–15 years), 32.7% middle adolescents (15–18 years), and 45.8% late adolescents (18–21 years). Among them, 38.3% were male and 61.7% were female. The results showed that there are various languages used by adolescents to express sad emotions, and adolescents tend to use nonverbal communication more often than language as verbal communication to express their sad emotions.